Relapses in multiple sclerosis are age- and time-dependent. Issue 12 (5th June 2008) - Tremlett, H; Zhao, Y; Joseph, J; Devonshire, V; ,
Abstract : Objectives: To examine the relative relapse-rate patterns over time in a relapsing multiple sclerosis (MS) cohort and to investigate potential predictors of relapse rates and periods of low-relapse activity. Methods: This retrospective cohort study followed 2477 relapsing-remitting (RR) MS patients from onset to 1 July 2003. Annualised relapse rates were examined according to sex, age at onset, the patient's current age and disease duration. The relationship between relapse rates and baseline characteristics (sex, onset age and onset symptoms) were examined using Poisson regression. Time to the first 5 years relapse-free was examined using Kaplan–Meier survival analysis. Results: The mean follow-up time (from onset of MS symptoms) was 20.6 years, during which time 11, 722 post-onset relapses were recorded. The relapse rate decreased by 17% every 5 years (between years 5 to 30 post-onset), but this decline increased in magnitude with increasing onset age. Women and those with onset sensory symptoms exhibited a higher relapse rate (p⩽0.001). More than three-quarters of patients (1692/2189) experienced a 5-year relapse-free period during the RR phase. Conclusion: Relapse rates were age- and time-dependent. Our observations have clinical implications: 1) any drug able to modify relapse rates has the greatest potential for a population impact in patients <40 years old and within the first few demi-decades of disease; 2) continuation of drug beyond these times may be of limited value; 3) long-term follow-up studies must consider that relapse rates probably decline at different rates over time according to the patient's onset age; 4) a relapse-quiescent period in MS is not uncommon.